ChemInform Abstract: Synthesis of Bulk Kesterite — A Prospective Photovoltaic Material. Issue 50 (16th December 2014) - Podisiadlo, Slawomir; Bialoglowski, Maciej; Matyszczak, Grzegorz; Marek, Paulina; Gebicki, Wojciech; Bacewicz, Rajmund; Stachowicz, Marcin; Dluzewski, Piotr; Wozniak, Krzysztof
Abstract Bulk single crystals of Cu2ZnSnS4 of kesterite structure with dimensions up to 1 x 1 x 0.5 mm are prepared from naturally abundant CuS, ZnS, and SnS in a molar ratio of 2:1:1 (evacuated quartz ampule, 700 °C, 24—240 h).